2016
DOI: 10.1155/2016/7235482
|View full text |Cite
|
Sign up to set email alerts
|

Viral Agents Causing Acute Respiratory Infections in Children under Five: A Study from Eastern India

Abstract: Background. Acute respiratory infections (ARIs) are important cause of mortality and morbidity in children under five in developing country. Methods. This observational study was conducted over two-year period in a tertiary care teaching hospital of Eastern India. Nasal and throat swabs were collected, transported to the laboratory at 2–8°C in viral transport media, and then processed for detection of viruses using mono/multiplex real-time polymerase chain reaction. Results. A total of 300 children aged 2–60 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 31 publications
4
21
1
Order By: Relevance
“…The most common respiratory viruses causing ARI were RSV, HMPV, PIV and HRV. These results are consistent with the viruses identified in this study [9,10]. Studies in hospitalized and outpatient pediatric patients worldwide have reported that HMPV is associated with 6-40% of acute respiratory illness [11].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The most common respiratory viruses causing ARI were RSV, HMPV, PIV and HRV. These results are consistent with the viruses identified in this study [9,10]. Studies in hospitalized and outpatient pediatric patients worldwide have reported that HMPV is associated with 6-40% of acute respiratory illness [11].…”
Section: Discussionsupporting
confidence: 91%
“…In Mexico, the circulation of HMPV was observed mainly in the northern and the central areas of the country where winter temperatures fluctuated between 5 • C and 7 • C, while in the areas of the southeast and the peninsula where the circulation of HMPV is lower, winter temperatures are higher (14 to 17 • C). The predominance of HMPV in the states with the lowest temperature in winter is consistent with a study that mentions that HMPV sees an increase in winter is due to the fact that the decrease in air temperature causes a decrease in nasal airway temperature (compromised cooling of the nasal airway), which leads to a poor defense against infection [9].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, respiratory pathogens could be categorized into four groups: single-infection of influenza A (39.4%), influenza B (21.7%), influenza, and multiple coinfections with two pathogens (21.7), three pathogens (12.0%), and four pathogens (5.2%). Studies conducted in Vietnam [24], Lao PDR [25], Japan [26], the Netherlands [27], and India [28] has reported both single and multiple respiratory infections were found more frequently in young children (<5 year). [35].…”
Section: Discussionmentioning
confidence: 99%
“…RSV-associated ALRI incidence ranging from 2.4% to 21.2% have been reported in different countries[21]. Hospital-based studies have reported a significant association between being male and having RSV-related ALRI[22]. Nair et al[5] concluded in a recent meta-analysis that RSV is the most common cause of childhood LRTI and a major cause of admission to hospital as a result of severe LRTI and that 99.0% of the RSV-related deaths take place among resource-limited countries.…”
Section: Discussionmentioning
confidence: 99%